1993
DOI: 10.1038/bjc.1993.428
|View full text |Cite
|
Sign up to set email alerts
|

A phase I and pharmacokinetic study of intraperitoneal carboplatin and etoposide

Abstract: Summary Background We attempted to determine the maximum tolerated dose and toxicity of etoposide (VP-16) when administered in combination with carboplatin (CBDCA) (300 mg m-2) and administered via the intraperitoneal (IP) route.Methods and Materials A total of 26 patients were treated on this trial. CBDCA was administered at a fixed dose of 300 mg m-2) while Material and methodsPatient eligibility and characteristics Patients were eligible for participation in this trial if they were 18 years of age or old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The magnitude of the intraperitoneal-to-plasma AUC ratio reflects the rate of carboplatin clearance from the peritoneal cavity relative to the clearance of carboplatin from the systemic circulation. The mean intraperitoneal-toplasma AUC ratio in our study corresponds well to the intraperitoneal-to-plasma AUC ratios reported from phase I studies with intraperitoneal administration of carboplatin, which is described to be in the range of 10-18 [8,[23][24][25]. Several individual physiological parameters can affect clearance from both compartments such as the size of the diffusion area, blood drainage to the peritoneal surfaces, and kidney function, which the broad range of the The peritoneal-plasma barrier prevents direct diffusion of the cytotoxic drug between blood and the peritoneal cavity.…”
Section: Discussionsupporting
confidence: 87%
“…The magnitude of the intraperitoneal-to-plasma AUC ratio reflects the rate of carboplatin clearance from the peritoneal cavity relative to the clearance of carboplatin from the systemic circulation. The mean intraperitoneal-toplasma AUC ratio in our study corresponds well to the intraperitoneal-to-plasma AUC ratios reported from phase I studies with intraperitoneal administration of carboplatin, which is described to be in the range of 10-18 [8,[23][24][25]. Several individual physiological parameters can affect clearance from both compartments such as the size of the diffusion area, blood drainage to the peritoneal surfaces, and kidney function, which the broad range of the The peritoneal-plasma barrier prevents direct diffusion of the cytotoxic drug between blood and the peritoneal cavity.…”
Section: Discussionsupporting
confidence: 87%
“…Carboplatin 500 mg/m 2 Thrombocytopenia, leukocytopenia 9 Markman et al (17) 13 Muggia et al (21) 1991 Floxuridine 3000 mg/body/days, for 3 days 2 to 4 log pharmacologic advantage 14 Oza et al (22) 1994 Mitoxiantrone 25 mg/m 2 Leukocytopenia, peritoneal irritation and pain 15 Plaxe et al (23) 1998 Topotecan 4 mg/m 2 Neutropenia 31.2 (AUC) 16 Sabbatini et al (24) 2004 Cisplatin, gemcitabine 75 mg/m 2 (fixed) 759 (AUC) for gemcitabine 17 Speyer et al (25) 1980 5-FU 4.5-5 mM Mucositis, pancytopenia 298 (peak) 18 Zimm et al (26) 1987 Cisplatin, etoposide 200 mg/m 2 (fixed), 350 mg/m 2…”
Section: Carboplatinmentioning
confidence: 98%
“…Therefore, IP chemotherapy using platinum agents can be hypothesized as one route of systemic chemotherapy. Table 2 summarizes results of phase I trials with or without pharmacokinetic study (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) . Among those agents, this section will discuss the pharmacology of IP cisplatin, carboplatin, and paclitaxel including animal experiments.…”
Section: Resistance To Solute Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacologic studies in the 1970s and 1980s demonstrated favorable profiles of high relative direct drug exposure (high C max and area under the dose response curve [AUC]) for a number of agents subsequently identified to be important for ovarian cancer treatment [10][11][12][13][14][15]. In this regard, both platinum (cisplatin and carboplatin) and taxanes (paclitaxel and docetaxel) have shown superior pharmacokinetic profiles when delivered into the peritoneum directly, compared with intravenous administration [10][11][12]. A sizeable number of phase I and II clinical studies have been performed in the past 35 years to document safety of this strategy and to suggest efficacy.…”
Section: Introductionmentioning
confidence: 99%